ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN KEMAMPUAN MATEMATIKA DAN GENDER - Sugiarti, Marselia; Siswanto, Rizki Dwi (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
This research aims to describe indicators of students' mathematical problem-solving ability in solving story problems related to derivative material in male and female students based on high, medium, and low mathematical abilities. This research is based on the importance of mathematical problem-solving skills and the low ability of students to solve problems, especially in story problems. This research used a qualitative descriptive method. The reduction of data that used is to group male and female students into three categories of mathematical abilities, namely high, medium and low abilities. The selection of research samples used purposive sampling techniques based on the consideration of the last value obtained by students on differential material. The research subjects consisted of 6 grade 11 students with criteria based on mathematical ability and gender. The results showed that only male students were able to meet the indicators of understanding the problem and drawing up a solution plan. Whereas on the indicators of carrying out the settlement, all subjects can write them down precisely. On the indicators of evaluating and drawing conclusions from the results obtained, only female students with low mathematical ability cannot write them down.